The Effect of Cognitive Behavioral Therapy (CBT)-Based Group Counseling on Culture Shock among Batak Students Studying Away from Home at UIN Mahmud Yunus Batusangkar - Rahma Sari Putri Tambunan; Darimis Darimis (Jurnal Counseling Care, 2025)
The aim of this study was to examine the effect of Cognitive Behavior Therapy-based group counseling on the culture shock experienced by Batak students studying away from home at UIN Mahmud Yunus Batusangkar. Culture shock is an emotional reaction to an individual's inability to adapt to a new environment. This study used a quantitative research design with a pre-experimental one-group pretest-posttest approach. The sample in this study consisted of new Batak students who were studying at UIN Mahmud Yunus Batusangkar. Data analysis was performed using the Wilcoxon test with SPSS. The results of this study showed that the level of culture shock among students before treatment tended to be high (60%) and moderate (40%) after treatment, indicating that culture shock among students was in the low category with a percentage of 100%. The results of the data analysis showed that the Asymp. Sig. value was < alpha, 0.043 < 0.05, so it can be concluded that group counseling based on Cognitive Behavior Therapy has an effect on the culture shock of Batak students at UIN Mahmud Yunus Batusangkar.